QUERCETIN NANOPARTICLES REPRESSED LIVER AND BRAIN TOXICITIES INDUCED BY TARTRAZINE IN RATS - Eman, G. Mohamed; Ibrahim, M. Abo-laila; Hassan, A.M. Hendawy; Ebtehal, Mohammad F (Journal of Drug Delivery and Therapeutics, 2018)
Tartrazine (TZ) is an azobenzene artificial yellow dye for foods, drugs, and cosmetics. Quercetin is member of the flavonoid family. The current study investigated the protective effect of quercetin nanoparticles (QNPs) against TZ. Male albino rats were divided into group1: control, group 2: TZ (50 mg/kg), group 3: QNPs (5 mg/kg), and group 4: QNPs+TZ. The results of the present study revealed that, the oral administration of TZ dye caused a significantly increased liver biomarkers. Also, a marked effect on lipid profile and blood parameters were shown. In addition TZ induced an elevation in the examined oxidative stress biomarkers and decrease in glutathione peroxidases and acetylcholine esterase. TZ diminished exploration and rearing in open field test as well as elevation in GABA content and apoptosis as well as changes in tissues by histopathological examination. In fact, the results showed good influence of QNPs in improving injuries associated with TZ administration. Keywords: Tartrazine Dye, Quercetin Nanoparticles, Liver-Brain injuries.